'I would say nine times out of 10 they come to the LSA rather than the teacher'. The role of teaching assistants in supporting children's mental health. Issue 3 (28th August 2021) - Conboy, Ida
Abstract : This research explored how seven primary school teaching assistants (TAs) experienced their role in supporting children's mental health. Interviews were analysed using Interpretative Phenomenological Analysis (IPA). The participants believed that they supported children's mental health and particularly referenced the close relationships that they formed with children. Throughout their accounts of supporting children, the TAs referenced helpful factors (e.g. support from other staff) and challenges (e.g. hierarchy) within the school system. Supporting children's mental health was an emotional experience for the TAs; they discussed the rewarding element, however, the topic also elicited fear. The findings provide several implications for school staff and external professionals about how TAs can be supported in their role. These include involving TAs in training opportunities, providing TAs with supervision, considering communication systems in schools, and introducing a mental health policy.